Harry Potter and the deathly hallows part 2 [video recording] / : hogwarts' last stand - Rowling, J.K. (Burbank, CA : Warner Home Video, 2011)
Harry Potter and the Deathly Hallows - Part 2 is the much awaited anticipated finale of a decade long Harry Potter film franchise that ends with an epic climactic battle between good and evil. Daneil Radcliffe, Rupert Grint, Emma Watson and all the filmmakers takes us on an adventure through the grounds of Hogwarts. From the immense coordination put forth from the cast and crew on the huge action sequences, to the careful planning on the many times intimate character moments that weave the story together, hear how this talented team made a landmark event - the battle for Hogwarts - truly epic.
Keywords: Potter, Harry (fictitious character) -- Drama